Application of Pulsed Electric Field During Malting: Impact on Fusarium Species Growth and Mycotoxin Production - Nela Prusova; Marcel Karabin; Lukas Jelinek; Jana Chrpova; Jaroslava Ovesna; Pavel Svoboda; Tereza Dolezalova; Adam Behner; Jana Hajslova; Milena Stranska (Toxins)
The increasing contamination of cereals by micromycetes and mycotoxins during malting still poses an unresolved food safety problem. This study characterises the potential of the novel, rapidly developing food production technology of Pulsed Electric Field (PEF) to reduce the viability of Fusarium fungi and the production of mycotoxins during malting. Barley, artificially inoculated with four Fusarium species, was treated by PEF with two different intensities and then malted using a standard Pilsner-type technology. Concentrations of fungi were quantified by RT-PCR, expression of fungal growth-related genes was assessed using mRNA sequencing, and mycotoxin levels were analysed by U-HPLC-HRMS/MS. Despite the different trends for micromycetes and mycotoxins after application of variously intense PEF conditions, significant reductions were generally observed. The greatest decrease was for F. sporotrichioides and F. poae, where up to six fold lower levels were achieved for malts produced from the PEF-treated barley when compared to the control. For F. culmorum and F. graminearum, up to a two-fold reduction in the PEF-generated malts was observed. These reductions mostly correlated with a decrease in relevant mycotoxins, specifically type A trichothecenes.